Modeling of the interfacial behaviors for the isobutane alkylation with C4 olefin using ionic liquid as catalyst. (20th July 2017) - Zheng, Weizhong; Xie, Wenxiu; Sun, Weizhen; Zhao, Ling
Highlights: ILs with various anions corresponding to different acidity were investigated. Anion density at hydrocarbon/IL interface was found higher than in the bulk. Butyl groups of cations tend to be perpendicular to the interface. As for acidic ILs, hydrocarbons are easier to disperse into the IL phase. Interactions between hydrocarbons and IL ions are fundamental to interface property. Abstract: As a typical liquid/liquid interface reaction, the isobutane alkylation with C4 olefins produces C8 alkylates that are important as clean gasoline components. In this work, the interfacial properties between the hydrocarbons (reactants and/or products) and 1-butyl-3-methylimidazolium ionic liquids (ILs) with various anions corresponding to different acidity, including [Bmim][PF6 ], [Bmim][BF4 ], [Bmim][AlCl4 ] and [Bmim][Al2 Cl7 ], have been investigated using molecular dynamics (MD) simulations. The density of the anions of ILs at interface was found to be about 10% higher than that in the bulk, which was favorable to the generation of carbonium at interface. The butyl groups of the cations tend to orient themselves perpendicular to the interface and protrude into the hydrocarbon mixtures phase, enhancing the dissolution of reactants at interface. It was also revealed that for the reactants, the molar fraction of 2-butene both in the bulk and at interface was much higher than that of isobutane, and 2-butene also had a larger diffusion coefficient at interface. However, for the product systems (isobutane + isooctane + IL), both the molar fraction and the diffusion coefficient of isobutane were obviously higher than that of isooctane. Compared to the neutral ILs, for the acidic ILs the binary hydrocarbon mixtures were easier to disperse into the IL phase with the mole fraction nearly 4 times higher in the bulk and about 1.2 times higher at interface. The difference in interfacial properties for various hydrocarbon-IL systems is in good agreement with the interaction energy between the hydrocarbons and the cations, as well as the anions of the ILs. Hopefully, the information concerning the IL-hydrocarbon interface at the molecular level obtained in this work can bring helpful insights into the C4 alkylation process catalyzed by the ILs.